An Analysis of Vertical Market Structures - Baligh, Helmy H.; Richartz, Leon E. (Management Science, 1964)
Models of vertical market structures are developed and solved for equilibrium numbers and levels of middlemen. The models investigate the behavior of contact and communication costs, and middlemen's profits in the system, under various market imperfections. When market imperfections are assumed away, the model gives an unrealistically large equilibrium number of middlemen and levels of middlemen. The removal of some assumptions by considering a) rebates given by middlemen in order to gain cooperation, b) segmented markets, c) costs of information transmittal, d) conditions of minimum returns on investment, and e) strategy formulation render the model more realistic.